THE CHARACTERISTICS OF OPTIMISTIC POSITION AND STRESS RESISTANCE IN HIGHER EDUCATION INSTITUTION STUDENTS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article examines the effect of optimistic and pessimistic attitude observed in students of higher education institutions on their susceptibility to stress and resilience to stress. The psychological characteristics of each position are analyzed and its impact on stress stability is highlighted.